OSTEOKONDROMA OF DISTALIS ULNAR WITH MASADA TIPE I DEFORMITY AMONG SEVEN YEARS OLD BOY: A CASE REPORT - Gustandra, Putu Gede Thurdy (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana, 2014)
Osteokondroma a benign tumor on the spine of the most common and manifests as a solitary non - hereditary exostosis is the long bone metaphysis in the majority of cases. Pain, impaired joint motion, tendon inflammation, as well as the compression of blood vessels and peripheral nerves is a complication caused by osteokondroma. Deformity is a frequent complication reported in osteokondroma that the bones of the lower arm (forearm). This report discusses the distal ulna osteokondroma on a male patient aged 7 years with shortening deformity of the ulna ( ulnar shortening ) according to the classification of type I. Masada Surgery ( excision of the tumor ) is the primary treatment option in this case . Forearm deformity subsequently corrected through the installation procedure with the ulnar lengthening plate fixation. Correction of the deformity provides improved cosmetic appearance of the forearm after surgery in these patients.
Keywords: osteokondroma , deformity , forearm , classification Masada